Mean temperature of the catch (MTC) in the Greek Seas based on landings and survey data - Tsikliras, Athanassios C.; Peristeraki, Panagiota; Tserpes, George; Stergiou, Konstantinos I. (Frontiers in Marine Science, 2015)
The mean temperature of the catch (MTC), which is the average inferred temperature preference of the exploited species weighted by their annual catch, is an index that has been used for evaluating the effect of sea warming on marine ecosystems. In the present work, we examined the effect of sea surface temperature on the catch composition of the Greek Seas using the MTC applied on the official catch statistics (landings) for the period 1970-2010 (Aegean and Ionian Seas) and on experimental bottom trawl survey data for 1997-2014 (southern Aegean Sea). The MTC of the landings for the study period increased from 11.8 οC to 16.2 οC in the Aegean Sea and from 10.0 οC to 14.7 οC in the Ionian Sea. Overall, the rate of MTC increase was 1.01 οC per decade for the Aegean and 1.17 οC per decade for the Ionian Sea and was positively related to sea surface temperature anomalies in both areas. For the survey data, the increase of the MTC of the bottom trawl catch in the southern Aegean Sea was lower (0.51 οC per decade) but referred to a shorter time frame and included only demersal species. The change in MTC of official and survey catches indicates that the relative catch proportions of species preferring warmer waters and those preferring colder waters have changed in favour of the former and that this change is linked to sea surface temperature increase, both internally (through the Atlantic Multidecadal Oscillation) or externally (warming trend) driven.